Uncovering Early Risk Factors of Diabetic Peripheral Neuropathy: Insights from Primary Health Care Facilities - Adelina Vidya Ardiyati; Ernawati; Ratna Pelawati; Dwi Setyowati; Septiyani Wijayanti (Jurnal Kesehatan Masyarakat, 2026)
Diabetic Peripheral Neuropathy (DPN) is a progressive and frequently underdiagnosed complication of type 2 diabetes mellitus. Limited early screening based on clinical risk factors in primary healthcare settings in Indonesia contributes to delayed diagnosis, increasing the likelihood of advanced neuropathy, foot ulceration, and lower-limb amputation. This study aimed to identify respondent characteristics and analyze risk factors associated with DPN among individuals with T2DM. A quantitative cross-sectional study was conducted among 162 patients with T2DM in the Bogor Primary Healthcare area. The Michigan Neuropathy Screening Instrument (MNSI) was used to assess neuropathic symptoms, and a physical foot examination was performed. Data were analyzed using Chi-square tests and binary logistic regression. The majority of respondents were aged 35–60 years (56.2%), female (69.1%), and had a duration of diabetes mellitus (DM) of <5 years (71.6%). 75.3% of respondents showed signs of Neuropathy, with the most common symptoms being dry and cracked skin on the feet (93.1%), muscle cramps (75.9%), and numbness (74.1%). No active ulcers were found (0%), and none had a previous diagnosis of Neuropathy. Bivariate analysis showed that age (p=0.004), duration of diabetes mellitus (p=0.030), and random blood sugar (p=0.000) were significantly associated with NPD. Logistic regression identified hyperglycemia (AOR=6.50; 95% CI = 2.65–15.85) and age ≥35 years (AOR=2.16; 95% CI 1.12–4.28) as independent predictors of NPD (Nagelkerke R²=0.27). Peripheral Neuropathy was highly prevalent even among patients with a short diabetes duration and had not been clinically diagnosed previously.